The Romantic subject as an absolutely autonomous individual - Cunta, Miljana (Acta neophilologica, 2004)
This essay deals with the Romantic subject as a philosophical and literary category. Recognizing the diversity and complexity of literary production in the Romantic period, this study does not attempt to treat all the many aspect sof this subject, but it instead focuses upon a few: the role of nature,the status of imagination, and the subject's relation to the transcendental reality. In its relation to these issues, the Romantic subject appears as an absolutely autonomous individual, one who finds no satisfaction in claims to transcendental certainty made by any source outside the self, but relies on his immanent powers to achieve the self-awareness that is the only sure access to truth. Special attention is given to the Romantic mystical experience, whereby the subject comes into relation with the transcendental reality. Here what are termed mystical feelings are contrasted with religious feelings proper so as to stress the peculiarities of the Romantic religious experience. In providing a theoretical framewok for the religious experience, we have recourse to Rudolf Otto's definition of the numinous, which denotes the feeling-response of the subject to the divine aspect of reality. In comparison with the true religious experience, the Romantic type is seen as pseudoreligious, thus confirming the proposed definition of the Romantic subject as a truly autonomous individual. The essay's second part contains an interpretation of selected poems by Samuel Taylor Coleridge with a view of extrapolating from them some aspects of the Romantic subject.
Keywords: Coleridge, Samuel Taylor, 1772-1834; filozofija književnosti; literarna teorija; literarne študije; literary theory; Romanticism; romantika